2011
DOI: 10.1021/bi100971y
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Rac Activation Domain in the Unconventional Guanine Nucleotide Exchange Factor Dock180

Abstract: Guanine nucleotide exchange factors (GEFs) activate Rho GTPases by catalyzing the exchange of bound GDP for GTP, thereby resulting in downstream effector recognition. Two metazoan families of GEFs have been described: Dbl-GEF family members that share conserved Dbl homology (DH) and Pleckstrin homology (PH) domains and the more recently described Dock180 family members that share little sequence homology with the Dbl family and are characterized by conserved Dock homology regions 1 and 2 (DHR-1 and -2). While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…Structural comparison of DOCK2 DHR2 -Rac1 and DOCK9 DHR2 -Cdc42 complexes indicates that Lys-27 sterically hinders the conformational change of switch 1 necessary for DOCK2 DHR2 -Rac interactions. Consistent with this notion, other studies showed that Rac2(A27K) is unable to bind DOCK2 (50) and that Rac(A27K) is only weakly activated by DOCK1 DHR2-C (47). However, replacing Lys-27 of Cdc42 with Ala is not sufficient to allow either DOCK2 DHR2 (Fig.…”
Section: Dhr2supporting
confidence: 72%
See 4 more Smart Citations
“…Structural comparison of DOCK2 DHR2 -Rac1 and DOCK9 DHR2 -Cdc42 complexes indicates that Lys-27 sterically hinders the conformational change of switch 1 necessary for DOCK2 DHR2 -Rac interactions. Consistent with this notion, other studies showed that Rac2(A27K) is unable to bind DOCK2 (50) and that Rac(A27K) is only weakly activated by DOCK1 DHR2-C (47). However, replacing Lys-27 of Cdc42 with Ala is not sufficient to allow either DOCK2 DHR2 (Fig.…”
Section: Dhr2supporting
confidence: 72%
“…The ability of either a Phe or Trp at position 56 to modulate the sensitivity of DOCKs for Rac and Cdc42 is also reminiscent of the striking activation of Rac1(W56F) by the Cdc42-specific DH-PH protein Intersectin (49), indicating a detrimental consequence of Trp-56 for Cdc42-specific GEFs. However, in contrast to findings that replacing Phe-56 with Trp renders Cdc42 responsive to the Rac-specific GEFs Tiam, GEF-H1, and TrioN (47-49), a previous study showed that Cdc42(F56W) was not activated by DOCK1 DHR2-C (47). Thus, factors additional to a Phe at position 56 are responsible for the inability of DOCK2 DHR2 to activate Cdc42.…”
Section: Dhr2mentioning
confidence: 68%
See 3 more Smart Citations